Acessibilidade aos pontos de ônibus : estudo de caso em São Carlos - Antunes, Juliana Carmo (Universidade Federal de São Carlos, 2010)
This work is the result of a research which subject is the accessibility to public transit at medium cities, being the case study applied at São Carlos-SP and its structures of access to the urban public transportation. It is an applied research, which aims to generate knowledge related to transportation and urban mobility studies. Taking into consideration aspects of exploratory and quantitative natures, it aims to provide familiarity to walking and pedestrian issues, and its relationship to public transit traveling. The finding results bring the main transit user s characteristics, and indicate the security issue as the one of most perception and relevance to people s choice, indicating that the creation of accessible routes is not related only to aspects of walking path, but also to urban design and social dynamics.
Keywords: Engenharia urbana; Acessibilidade; Transportes -planejamento; Transporte coletivo; Pedestres; Coleta de dados; Instrumentos de auditoria; Instrumentos de coleta de dados; Entrevistas; Accessibility; Public transit; Pedestrian; Data collection; Audit tools; Data survey instruments; Interviews; ENGENHARIAS